Gamma Delta T Cells and Their Pathogenic Role in Psoriasis - Qi, Cong; Wang, Yazhuo; Li, Ping; Zhao, Jingxia (Frontiers in Immunology, 2021)
γδT cells are an unconventional population of T lymphocytes that play an indispensable role in host defense, immune surveillance, and homeostasis of the immune system. γδT cells display unique developmental, distributional, and functional patterns. They rapidly respond to various insults and contribute to diverse diseases. Although γδT cells make up only a small portion of the total T cell pool, emerging evidence suggest that aberrantly activated γδT cells may play a role in the pathogenesis of psoriasis. Dermal γδT cells are the major IL-17-producing cells in the skin that respond to IL-23 stimulation. Furthermore, γδT cells exhibit memory cell characteristics that mediate repeated episodes of psoriatic inflammation. This review discusses the differentiation, development, distribution, and biological function of γδT cells and the mechanisms through which they contribute to psoriasis. Potential therapeutic approaches targeting these cells in psoriasis have also been detailed.